Detection of Healthcare Bubbles in Iran: a Left-Tailed Augmented Dickey-Fuller (LTADF) Approach - Khodabakhshzadeh, Saeed; ZAYANDEHROODI, Mohsen; ESFANDABADI, Seyyed Abdolmajid Jalaee (International Journal of Contemporary Economics and Administrative Sciences, 2018)
Healthcare bubbles can cause instability in healthcare system. This study investigates the possibility of single and multiple healthcare bubbles in Iran healthcare market. We applied ADF, SADF and GSADF methods of Left-Tailed Augmented Dickey-Fuller to locate single and multiple healthcare bubble episodes. In particular, this study focuses on the explosive behavior of the pharmaceutical products indicator in the Tehran Stock Exchange (TSE) from November 2008 to August 2017. Our results show that the Iran healthcare market has experienced 8 bubbles over the period of 2008-2017, some of which are single, and others are multiple. The first bubble has occurred in June 2010. Other healthcare bubbles have appeared from 2011 until August 2014. However, the seventh bubble appears two years later in August 2016. The peak in healthcare bubbles can be seen in March to April in 2013. Healthcare policymakers should monitor the market to recognize the bubbles so that they can mitigate the consequences of the bubble in the market and orient the prices of medical and pharmaceutical commodities